ICT for the Teaching-Learning Process in Physics Laboratories at the University Level in the State of Trujillo, Venezuela - Rosario, Jesús Ramón; Lobo, Hebert; Rivero, Dilue; Briceño, Jesús; Villarreal, Manuel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
We report preliminary results of descriptive research, with field design to identify and evaluate the use of Infor-mation and Communication Technologies (ICT) in physics laboratories of universities, public and private, in the state of Trujillo Venezuela, based pilot study center at the Universityof Los Andes, Faculty Rafael Rangel degree in Physical Educa-tion and Mathematics. Regarding the use of technology platforms, virtual environments and interactive teaching materials as an auxiliary tool in the teaching-learning process provided for students and teachers, such as software, simulators, blog, websites, forums, emails, videos, presentations, and more. We applied a survey type instrument with open and closed questionswith a numerical rating scale, questionnaires with multiple choice answers to students and teachers in physics laboratories and instrument of observation and evaluation of interactive tools used. With the obtained results confirm the relevance of the work preliminary hypothesis is generally established the reliability and validity of the data collection instruments.